Changes of the surface air temperature in the 20th – 21st centuries in the Antarctic Peninsula region based on climate models’ datа - Krakovska, S.V.; Pysarenko, L.A. (Ukrainian Antarctic Journal, 2017)
This paper is dedicated to surface air temperature dynamics in the Antarctic region where the most rapid warming on the Earth was recorded during the second half of the 20th century. As air temperature is one of the main characteristics of climate system and climate model is the only tool to forecast future climate change, temperature data of Atmospheric-Ocean Global Circulation Models (AOGCMs) and measurements at the Ukrainian Antarctic Akademik Vernadsky station (former British Faraday station) were used for this research. Therefore, the main objectives of the research were to verify of 10 AOGCMs and their ensemble in comparison with observational data in period 1947-2016 at the station; to extract and to analyze climate projections till the end of the 21st century for the Antarctic Peninsula region based on scenarios of the 4th (SRES) and 5th (RCP) Reports of the Intergovernmental Panel on Climate Change (IPCC). Overall 93 model runs of 10 AOGCMs were analyzed. Comparative analysis between SRES and RCP IPCC scenarios of air temperature change has been performed and demonstrated, as a result, an absence of strong contradiction between the respective scenarios in surface air temperature projections both on global scale and in the Antarctic region. The verification of 10 AOGCMs runs has been carried out with 70-year observational data from Ukrainian Antarctic Akademik Vernadsky station where temperature has been increasing with rate of 0.51°С/10 years. Similar coefficients of linear trend and high correlation between measured air temperature at the station and in AOGCMs have confirmed that these climate models can be used for obtaining air temperature projections in the future. As a conclusion, analysis of climate projections for 21st century of 10 AOGCMs and their ensembles has demonstrated further temperature increase for all the above scenarios. The most rapid warming in the studied region has been expected for “pessimistic” A2 scenario with average temperature rise 0.29°С/10 years, “balanced” A1B scenario has projected 0.26°C/10 years and “optimistic” B1 – 0.15°C/10 years.